Research handbook on intellectual property and cultural heritage - Stamatoudi, Irini A. (Research handbooks in intellectual property series, 2022)
"This important Research Handbook offers a comprehensive analysis of the intersections between intellectual property (IP) and cultural heritage law. It explores and compares how both have evolved and sometimes converged over time, how they increased tremendously in significance, as well as in economic value, despite the fact that the former mainly pertains to the private sphere, whilst the latter is considered a 'common good'. Featuring an excellent combination of contributions from leading experts, chapters offer insights into relevant cutting-edge issues that still remain unsettled. Divided into three main parts, it focuses on how IP can work as a tool for cultural heritage protection and in particular, intangible cultural heritage, and discusses the politics and policies in this area, including whether such protection is fit for purpose. The final section explores special issues of intersection between the two making it relevant to cultural heritage institutions such as museums, galleries, auction houses, libraries, and platforms, including issues of cultural heritage and IP management. Encompassing the latest developments and debates in the area, this Research Handbook will be key reading for academics, post graduate students and researchers in the fields of cultural heritage and art law, cultural heritage management, and intellectual property law. It will also be relevant for practitioners, policy makers, cultural heritage institutions, and content platforms"--